2012
DOI: 10.31258/jnat.13.3.232-236
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Agronomic Traits of Centella asiatica (L.) Urban. Naturally Grown at Regions With Different Altitudes

Abstract: The Centella asiatica is an important herbal plant in Indonesia. The research was done to describe several agronomic traits that related to yield of the plants grown at regions with different altitudes. The research was carried out at three different regions of highland, midland, and lowerland, each at >500m, 250-500m, and < 250m above sea level. The research location was Pagar Alam, Musi Rawas, and Ogan Ilir, respectively. Research indicated that the agronomic traits of the plants grown at highland, midland, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A dose of 81 kg ha−1 at an altitude of 450 m asl gave the highest fresh weight yield, but it was not significantly different than a dose of 54 at an altitude of 900 m asl. Halimi [33] stated that was an indication that the leaves of the plants grown in mid-and highland regions were larger in size with shorter petiole compared to plants in lower regions. The increase in P fertilizer would increase the dry weight of C. asiatica and the content of asiaticoside [34,35].…”
Section: Performance Growth and Productivity Of C Asiaticamentioning
confidence: 99%
“…A dose of 81 kg ha−1 at an altitude of 450 m asl gave the highest fresh weight yield, but it was not significantly different than a dose of 54 at an altitude of 900 m asl. Halimi [33] stated that was an indication that the leaves of the plants grown in mid-and highland regions were larger in size with shorter petiole compared to plants in lower regions. The increase in P fertilizer would increase the dry weight of C. asiatica and the content of asiaticoside [34,35].…”
Section: Performance Growth and Productivity Of C Asiaticamentioning
confidence: 99%
“…However, the wild stock of C. asiatica has been markedly depleted due to large scale and unrestricted exploitation with very limited cultivation [10]. Halimi [11] reported that C. asiatica can be grown in lowland, midland, and highland in Indonesia. However, C. asiatica required sufficient nutrient availability for obtaining high yield and maintaining the quality of its active principles [12].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, C. asiatica (L.) is a small perennial herbal plant with kidney-shaped leaves that belongs to the family Apiceae [10]. It grows in damp and swampy areas of tropical countries and is commonly known as pegaga in Malaysia, Indian Pennywort in the United States of America, yuhong-yuhong in the Philippines, tapak kuda in Indonesia and buak bok in Thailand [11, 12]. It has various therapeutic activities that are mainly attributed to its biologically active ingredients, i.e.…”
Section: Introductionmentioning
confidence: 99%